Improvement of osseointegration of Ti-6Al-4V ELI alloy orthodontic mini-screws through anodization, cyclic pre-calcification, and heat treatments - Changkyun Im; Je-Hyeok Park; Young-Mi Jeon; Jong-Ghee Kim; Yong-Seok Jang; Min-Ho Lee; Woo-Yong Jeon; Jun-Min Kim; Tae-Sung Bae (SpringerOpen, 2022)
Abstract Background Mini-screws are widely used as temporary anchorages in orthodontic treatment, but have the disadvantage of showing a high failure rate of about 10%. Therefore, orthodontic mini-screws should have high biocompatibility and retention. Previous studies have demonstrated that the retention of mini-screws can be improved by imparting bioactivity to the surface. The method for imparting bioactivity proposed in this paper is to sequentially perform anodization, periodic pre-calcification, and heat treatments with a Ti-6Al-4V ELI alloy mini-screw. Materials and methods A TiO2 nanotube-structured layer was formed on the surface of the Ti-6Al-4V ELI alloy mini-screw through anodization in which a voltage of 20 V was applied to a glycerol solution containing 20 wt% H2O and 1.4 wt% NH4F for 60 min. Fine granular calcium phosphate precipitates of HA and octacalcium phosphate were generated as clusters on the surface through the cyclic pre-calcification and heat treatments. The cyclic pre-calcification treatment is a process of immersion in a 0.05 M NaH2PO4 solution and a saturated Ca(OH)2 solution at 90 °C for 1 min each. Results It was confirmed that the densely structured protrusions were precipitated, and Ca and P concentrations, which bind and concentrate endogenous bone morphogenetic proteins, increased on the surface after simulated body fluid (SBF) immersion test. In addition, the removal torque of the mini-screw fixed into rabbit tibias for 4 weeks was measured to be 8.70 ± 2.60 N cm. Conclusions A noteworthy point in this paper is that the Ca and P concentrations, which provide a scaffold suitable for endogenous bone formation, further increased over time after SBF immersion of the APH group specimens. The other point is that our mini-screws have a significantly higher removal torque compared to untreated mini-screws. These results represent that the mini-screw proposed in this paper can be used as a mini-screw for orthodontics.